Stable Isotope Turnover and Fractionation of Different Feed in the Juvenile Scylla paramamosain - Shengping ZHONG; Xiaohui CAI; Jianda SONG; Xujia LIU; Yinhui PENG; Lianghua HUANG; Changzi GE; Guoqiang HUANG (Progress in Fishery Sciences)
Investigating the effects of different diets on carbon and nitrogen stable isotope turnover and fractionation coefficients in juvenile green crabs (Scylla paramamosain), we used 200 tanks measuring 50 × 40 × 40 cm. Fish (Callionymus richardsoni), shrimp (Penaeus latisulcatus), clam (Ruditapes philippinarum), and polychaeta worms (Perinereis aibuhitensis) were fed to the juvenile crabs whose initial weight is 1.5 g. Samples were collected at 0, 30, 60, 90, 135, and 180 d to determine the δ13C and δ15N and calculate turnover parameters as well as fractionation coefficients. Our findings described that the differences in the juvenile crabs' δ13C and δ15N during the experimental period were demonstrated by δ13C = a × lnt + b and δ15N = a × lnt + b, where the value of "a" varied significantly with the different diets. Growth is the main factor driving carbon and nitrogen-stable isotopic turnover in juvenile crabs. The contributions of the four diets (fish, shrimp, clam, and crab) to the 13C turnover of the crabs were 79.83%, 83.65%, 84.88%, and 63.80%, respectively, whereas their contributions to the 15N turnover were 81.97%, 82.88%, 75.27%, and 59.80%, respectively. Our findings indicated a clear difference in the stable isotope turnover of juvenile green crabs, which was primarily metabolism-induced. The significant difference in growth rates between the two studies inevitably led to differences in the assimilation and deposition rates of carbon and nitrogen in their body, causing differences in the contributions of growth and metabolism to the turnover of stable isotopes. The time to complete 50% turnover (t50) of 13C and the time to complete 95% turnover (t95) for crabs fed the four diets were 36.30, 24.56, 27.96, 21.17 d and 156.86, 106.16, 120.83, 91.64 d, respectively. The t50 of 15N and t95 for crabs fed the four diets were 37.60, 24.34, 24.77, 20.17 d and 162.49, 105.22, 107.05, 86.99 d, respectively. The results of this experiment indicate that the t50 values of 13C and 15N in juvenile fiddler crabs fed the same diet were similar, and the t95 values were more than four times higher than the t50 values, indicating that the turnover rates of stable isotopes were high in the early stages of the experiment and decreased significantly in the later stages. The fractionation coefficients Δ13C180d for crabs fed the four diets at 180 d ranged from 0.71‰ to 1.64‰, and the Δ15N180d ranged from 2.15‰ to 2.66‰. Overall, the measured value of Δ13C180d is closer to the literature-cited value of 1.3‰, while the measured value of Δ15N180d was incongruent with the literature-cited value of 3.4‰. Since the large range of fractionation factors for stable isotopes in bait materials among consumers in nearshore and estuarine ecosystems, caution should be exercised when citing fractionation factors in related ecological studies, and actual measurements or data from identical or similar species under similar environmental conditions should be used whenever possible. The relationship between Δ13C and mass growth rate (MGR, %) followed the formula Δ13C = a × ln(MGR) + b, and the relationship between Δ15N and MGR followed the formula Δ15N = a × ln(MGR) + b, with significant variations in the values of "a" and "b" when consuming different diets. Δ13C showed a negative linear correlation with the δ13C of the diets, and a positive linear correlation with the difference in δ13C values between the initial juvenile crabs and diets (δ13CIC–δ13CD). Δ15N demonstrated a negative linear correlation with the δ15N of the diets, and a positive linear correlation with the difference in δ15N values between the initial juvenile crabs and diets (δ15NIC–δ15ND). The diet quality and stable isotope content were the main factors affecting fractionation. Although the δ13C and δ15N of the crabs during the experiment approach and ultimately maintain a level higher than that of the diet, the fractionation factor remains influenced by the δ13C and δ15N of the diet. We concluded that growth was the main driving factor for stable isotope turnover in juvenile green crabs and that the stable isotope abundance of the diets was an important factor affecting the fractionation coefficients. The findings of this study provide reference data for nutritional ecology research on green crabs.